WALKING THE TIGHTROPE: CHALLENGES ENCOUNTERED IN NOVICE TEACHERS' PRACTICE - Miruna Luana Miulescu (National Centre for Policy and Evaluation in Education, 2020)
The first years of teaching experience are crucial for beginning teachers as they face numerous challenges. Moreover, the way novices succeed in handling challenges during their first year of field work is a key determinant of their decision to continue working in the system or not. In this respect, a notable theme within the literature considers the experiences and challenges of beginning professionals, as more and more researchers talk about the "praxis shock", "reality shock" or "transition shock" to better depict the process through which new teachers pass in order to get accustomed to their new professional context. Our study seeks to investigate the challenging experiences that novice kindergarten teachers encounter, as well as the strategies they adopt in order to overcome them. The participants of the present study are beginning teachers (n=16) with a maximum of three years' teaching experience from six public inner-city kindergartens. By making use of a phenomenological qualitative inquiry, data was collected through participating at semi-structured interviews, focus groups and by filling in logbooks. After the data was recorded and transcribed, five main themes were identified. The key findings indicate that a new professional context can often lead to uncertainty and discomfort. Moreover, beginning teachers' "challenging moments" descriptions generally emphasize their struggles concerning their own professional development, the school organizational aspects, as well as their relationships with students, colleagues, principals and parents. The results of the study show the need to restructure the collaboration process between novices and kindergartens, in order to improve collaborative relationships and provide the appropriate context for the professional development of kindergarten teachers at the beginning of their careers.